Economic and development alternatives from epistemologies of the South and certain new worldviews - Fuentes González, José Andrés (Cooperativismo & Desarrollo, 2016)
Purpose: This article is written in the context of a regional struggle for the construction of autonomies, liberated spaces, and a defense of territory and our Mother Earth. The search for alternatives in these times of global crisis is urgent. However, we do not need alternatives but rather a new mode of knowledge production, i.e., an alternative way of thinking about alternatives. Description:In this article, we will discuss the case of Yomol A’tel (a group of solidarity economy cooperatives and enterprises in Chiapas, Mexico), which seeks to base itself on the Tzeltal indigenous worldview to find other ways of doing economics and of understanding work and production. Viewpoint:The economy, development, and all institutions of industrial society are daughters of the modern ego: it is this that is in crisis and in question. Conducting our analyses and research from different epistemic premises will lead us to distinct conclusions; reality shifts depending on the language used to inquire about it. Conclusions: Both epistemologies of the South and other new worldviews can enter into a dialogue of knowledges and be the basis for the construction of a new and relevant way of knowing.